MENINGKATKAN KEMAMPUAN BACA TULIS AL-QUR’AN MELALUI TUTOR SEBAYA: Penelitian Tindakan Kelas Pada Kelas VII K di SMPN 1 Bojongpicung - NURBAETI NURBAETI (MGMP PAI Jawa Barat, 2022)
At the junior high school level, students should have mastered the competence of being able to read the Koran and master some of the laws of recitation. However, the reality in the field is that there are still many students who have not mastered reading and writing the Qur'an and are even completely illiterate. Of course, this causes the opportunity to develop the ability of students to read and write the Koran cannot be carried out optimally. So that is the background of this research. The formulation of the problem and the purpose of this research is to determine the extent to which the improvement of Al-Quan literacy skills through peer tutoring methods. This research method uses a classroom action research approach to class VII K SMPN 1 Bojongpicung with a total of 30 students. The optimal role of the teacher is shown in the increase in the quality of doing learning which reaches 92.31% compared to the first cycle, which is 71.15%. The data on the activity of the second cycle increased from the first cycle, as seen in the observations of the tutor's activity which reached 96.67% and the increase in the activity of group members which reached 69.33%. While the increase in student activity is very influential on improving learning outcomes, it is proven after the evaluation test cycle II was classical completeness reached 100%. Thus, there is a significant increase in the ability to read and write the Koran through this peer tutoring method.